An Analysis of Clinical Characteristics of Rare Bilateral Cerebral Peduncular Infarction - Chen, Hao; Hu, Qian; Raza, Hafiz Khuram; Singh, Sandeep; Rai, Pabitra; Zhu, Jienan; Cui, Guiyun; Ye, Xinchun; Xu, Chuanying; Jing, Jia; Liu, Yonghai (Frontiers in Neurology, 2019)
Objective: To investigate the anatomical characteristics, clinical manifestations and imaging features of bilateral cerebral peduncular infarction. Methods: A retrospective analysis was performed on 11 patients diagnosed with bilateral cerebral peduncular infarction in the Affiliated Hospital of Xuzhou Medical University from December 2014 to December 2018. Their clinical and imaging features were analysed and summarized in combination with the relevant national and international literature. Results: Among all the patients, there were 8 cases with a history of hypertension, 4 cases with a history of diabetes mellitus, and 4 cases with a history of smoking. Conscious disturbance was observed in 9 cases, quadriplegia in 7 cases, pseudobulbar paralysis in 3 cases, and ataxia in 1 case. Brain magnetic resonance (MR) scans of bilateral cerebral peduncles showed patchy abnormal shadows with a hypointense signal on T1-weighted imaging (T1WI) and apparent diffusion coefficient (ADC) and hyperintense signal on T2-weighted imaging (T2WI), fluid attenuated inversion recovery (FLAIR), and diffusion-weighted imaging (DWI). Computed tomography angiography (CTA) scans of head and neck showed severe stenosis or occlusion of vertebral artery, basilar artery, or posterior cerebral artery. All the patients received standardized treatment for cerebral infarction. 6 patients died while 5 were left disabled. Conclusion: Bilateral cerebral peduncles infarction may be related to cerebral perfusion insufficiency caused by the stenosis or occlusion of vertebrobasilar artery and its branches. The main clinical manifestations are locked-in syndrome and persistent vegetative state. The specific imaging feature of "Mickey Mouse ear" - like infarction is associated with a poor prognosis.